Investors controlling 6.5 trillion USD ask fast food companies to reduce greenhouse gas emissions from agriculture - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
A network of investors controlling 6.5 trillion USD demanded that fast food companies reduce emissions from their supply chains, informed by CCAFS advising on options to monitor and mitigate emissions from beef and dairy production. The outcome was the result of a collaboration between CCAFS and Ceres, an advocacy NGO that provides advisory services to investors.